100 Books Every Blues Fan Should Own - Komara, Edward; Johnson, Greg (Rowman & Littlefield Publishers, 2014)
Search the Internet for the 100 best songs or best albums. Dozens of lists will appear from aficionados to major music personalities. But what if you not only love listening to the blues or country music or jazz or rock, you love reading about it, too. How do you separate what matters from what doesn’t among the hundreds—sometimes thousands—of books on the music you so love? In the Best Music Books series, readers finally have a quick-and-ready list of the most important works published on modern major music genres by leading experts. In 100 Books Every Blues Fan Should Own, Edward Komara, former Blues Archivist of the University of Mississippi, and his successor Greg Johnson select those histories, biographies, surveys, transcriptions and studies from the many hundreds of works that have been published about this vital American musical genre. Komara and Johnson provide a short description of the contents and the achievement of each title selected for their “Blues 100.” Entries include full bibliographic citations, prices of copies in print, and even descriptions of specific editions for book collectors. 100 Books Every Blues Fan Should Own also includes suggested blues recordings to accompany each recommended work, as well as a concluding section on key reference titles—or as Komara and Johnson phrase it: “The Books behind the Blues 100.” 100 Books Every Blues Fan Should Own serves as a guide for any blues fan looking for a road map through the history of—and even history of the scholarship on—the blues. Here Komara and Johnson answer the question of not only what is a “blues” book, but which ones are worth owning.